2022
DOI: 10.1038/s41420-021-00793-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SND1-IT1 facilitates TGF-β1-induced epithelial-to-mesenchymal transition via miR-124/COL4A1 axis in gastric cancer

Abstract: The transformation of tumor cells from an epithelial to a mesenchymal-like phenotype, designated as epithelial-to-mesenchymal transition (EMT), represents a key hallmark of human cancer metastasis, including gastric cancer (GC). However, a large set of non-coding RNAs have been studied for their functions that initiate or inhibit this phenotypic switch in GC cells by regulating oncogenes or tumor suppressors. In this paper, we aimed to identify lncRNA SND1-IT1, miR-124, and COL4A1 gene in the context of GC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Conversely, collagens bind to integrins, discoidin domain receptors and tyrosine kinase receptors to influence the behavior of tumor cells ( 27 ). COL4A1, which belongs to the collagen family, serves a tumor-promoting role in several types of cancer ( 28 , 29 ). Wang et al ( 30 ) showed that COL4A1 exerts a promoting effect on proliferation and metastasis in hepatocellular carcinoma via the activation of a FAK-Src signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, collagens bind to integrins, discoidin domain receptors and tyrosine kinase receptors to influence the behavior of tumor cells ( 27 ). COL4A1, which belongs to the collagen family, serves a tumor-promoting role in several types of cancer ( 28 , 29 ). Wang et al ( 30 ) showed that COL4A1 exerts a promoting effect on proliferation and metastasis in hepatocellular carcinoma via the activation of a FAK-Src signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it induces M2 polarization of macrophages and facilitates the proliferation, migration, and angiogenesis of cholangiocarcinoma (Deng et al, 2022). COL4A1 and IGFBP4 can also promote EMT of multiple types of cancer and enhance their migration and invasion (Hu et al, 2022; Praveen Kumar et al, 2014; Zhang et al, 2021). In this study, we found that OCAFs with FERMT2 knockdown had significantly weakened EMT‐inducing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SND1-IT1 accelerates cell proliferation, migration, and invasion in retinoblastoma [ 21 ]. The transcript also plays a role in epithelial-mesenchymal transition in gastric cancer [ 22 ]. Our results showed that SND1-IT1 interacts with ATXN2L, DSTN, SUGT1, SEPT3, and BDH1 genes.…”
Section: Discussionmentioning
confidence: 99%